Aeromonas spp. as a Causal Agent of Acute Diarrhetic Syndrome in Children Under Six Years of Age - Luzmila Albarado; Ivonne Samper; Militza Guzmán (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Diarrhea represents a serious public health problem, and bacteria is one of the most frequent causes of the same, which requires the need to select an effective bacteriological diagnosis. In order to determine the frequency of Aeromonas spp. as a causal agent of gastrointestinal illnesses, a study was carried out in patients under 6 years of age with acute diarrheic syndrome, who were attended in the pediatric emergency service at the Antonio Patricio de Alcalá University Hospital (SAHUAPA), in Cumaná, Sucre state. For this study130 stool samples were collected during the period of May to September 2002, and a microbiological study of the samples was carried out through copro-culture and the antimicrobial susceptibility test using the disk diffusion method. Of the total number of samples analyzed, a positive response was obtained in 24,60%; of which 12,5% corresponded to Aeromonas spp. The species of the Aeromonas gender that were identified were were A. caviae, A. hydrophila and A. sobria. Aeromonas caviae was the most frequent, representing 50% of the isolated species. The distribution for age placed the species of Aeromonas spp. in the 1 to 4 year age group, and more specifically in the age group of 1 to 2 years where three of the four isolates were located. In relation to antimicrobial susceptibility, all the isolates of Aeromonas spp. were sensitive to chloramphenicol at 100,00% and to trimetroprim-sulfamethoxazole at 75,00%. They showed resistant to cefalotin at 75,00%. The results obtained in this research indicate that Aeromonas spp. presented a low frequency and ease of treatment with antimicrobials; however, due to their clinical and microbial repercussion, their identification in intestinal samples is justified.